2018
DOI: 10.1042/bsr20171252
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intracellular signaling pathways orchestrate adipocytic differentiation of human bone marrow stromal stem cells

Abstract: Bone marrow adipocyte formation plays a role in bone homeostasis and whole body energy metabolism. However, the transcriptional landscape and signaling pathways associated with adipocyte lineage commitment and maturation are not fully delineated. Thus, we performed global gene expression profiling during adipocyte differentiation of human bone marrow stromal (mesenchymal) stem cells (hMSCs) and identified 2,589 up-regulated and 2,583 down-regulated mRNA transcripts. Pathway analysis on the up-regulated gene li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…Cell division, DNA replication, mitotic nuclear division, G1/S transition of mitotic cell cycle and DNA replication-dependent nucleosome assembly were the top five biological function (BP) terms related to cell cycle and cell division. The present study found that genes involved in these categories were mostly down-regulated, in agreement with previous studies (Ali et al, 2018;Menssen et al, 2011). In order to obtain more significant GO terms, we performed analysis on the top 200 DEGs with lower p values.…”
Section: A a A A A A A A A A A A A A A A A A A A A A A A A A A A A D D Dsupporting
confidence: 92%
See 1 more Smart Citation
“…Cell division, DNA replication, mitotic nuclear division, G1/S transition of mitotic cell cycle and DNA replication-dependent nucleosome assembly were the top five biological function (BP) terms related to cell cycle and cell division. The present study found that genes involved in these categories were mostly down-regulated, in agreement with previous studies (Ali et al, 2018;Menssen et al, 2011). In order to obtain more significant GO terms, we performed analysis on the top 200 DEGs with lower p values.…”
Section: A a A A A A A A A A A A A A A A A A A A A A A A A A A A A D D Dsupporting
confidence: 92%
“…0A 0A 0A 0A 0 0 0 0 0A 0A A A A A 0A 0A A A 0A 0A A 0A 0A 0 0A 0 0 0 0A 0 0A A 0A A A A 0A A 0A A 0 0 0A 0A A 0 0 0 0A 0 0 0A A 0A 0 0A A A 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 between BMA and osteogenic lineage is still a mystery. Global gene expression profiling by Ali et al (2018) using microarray assay on day 7 after adipogenic differentiation of hMSC-TERT identified FAK and IGF1R signaling as important pathways during bone marrow adipogenesis. However, intrinsic connection of DEGs remains unexplored.…”
Section: A a A A A A A A A A A A A A A A A A A A A A A A A A A A A D D Dmentioning
confidence: 99%
“…Furthermore, adipogenic differentiation of human bone marrow stromal stem cells was shown to be associated with up-regulation of SELENOF, -M, -P, and SELENBP1, along with FABP4, ADIPOQ, and C/EBPα. Se metabolism pathway was considered as one of the top ten enriched pathway categories [143]. Correspondingly, in pigs feeding a HFD reduced selenoprotein mRNA expression in perirenal adipose tissue (SELENOH, -K, -P, -V, and -W) and SAT (SELENOI, -M, and MSRB1) [30].…”
Section: Adipose Tissue As a Target For Se Activity: Adipocyte Selenomentioning
confidence: 99%
“…Insulin and insulin-like growth factors (IGF) are evolutionarily highly conserved proteins that play an important role in growth and metabolism, but also in neurogenesis through their role in neuronal stem-cell homeostasis (reviewed in Lee et al, 2016 ; Ali et al, 2018 ). In Drosophila , expression of dFMR1 specifically in the insulin-producing cells (IPSs) or in the whole nervous system is able to rescue the defective free-running locomotor rhythmicity of dFMR1 mutants, as well as short-term and long-term memory defects in olfactory learning tests (Monyak et al, 2016 ).…”
Section: Successful Pharmacological Treatments Of Fxs Phenotypes In mentioning
confidence: 99%